PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGANPADA PERUSAHAAN PERSEWAAN ALAT BERAT PT. PETROKOPINDO CIPTA SELARAS - Devi Norfinahari; Moh. Agung Surianto (Yayasan Nusantara Hasana Berdikari, 2025)
With the rise of development in Gresik City, the demand for heavy equipment to support the development process is also increasing. PT PCS needs to become a company providing logistics facilities and other services that is the first choice for customers by supporting the provision of logistics facilities thet prioritize customer satisfaction. So, this research can help companies find out the level of customer satisfaction and what aspects of service quality can influence customer satisfaction. The research method used in this case is a quantitative method. The population used is customers who have used heavy equipment rental services at PT.PCS, while the sampling technique used was census. The data used was processed using SPSS with multiple linear regression data analysis techniques. There are 5 dimensions of service quality used, namely: physical evidence, reliability, responsiveness, assurance and emphaty. The research results show that there is a relationship in the heavy equipment sector at PT PCS in 2024.